Lfc subcellular localization and activity is controlled by αv-class integrin - Colo, Georgina Pamela (2023)
Fibronectin (FN)-binding integrins control a variety of cellular responses through Rho GTPases. The FN-binding integrins, αvβ3 and α5β1, are known to induce different effects on cell morphology and motility. Here, we report that FN-bound αvβ3 integrin, but not FN-bound α5β1 integrin, triggers the dissociation of the RhoA GEF Lfc (also known as GEF-H1 and ARHGEF2 in humans) from microtubules (MTs), leading to the activation of RhoA, formation of stress fibres and maturation of focal adhesions (FAs). Conversely, loss of Lfc expression decreases RhoA activity, stress fibre formation and FA size, suggesting that Lfc is the major GEF downstream of FN-bound αvβ3 that controls RhoA activity. Mechanistically, FN-engaged αvβ3 integrin activates a kinase cascade involving MARK2 and MARK3, which in turn leads to phosphorylation of several phospho-sites on Lfc. In particular, S151 was identified as the main site involved in the regulation of Lfc localization and activity. Our findings indicate that activation of Lfc and RhoA is orchestrated in FN-adherent cells in an integrin-specific manner.